(untitled) (Archives of Pediatrics of Uruguay, 2022)
We hereby present the case of a newborn with early connatal sepsis due to Streptococcus agalactiae, with acute suppurative meningitis and left knee osteoarthritis. As a risk factor, the mother had not performed the rectus vaginal exudate screening that detects colonization by Group B Streptococcus (GBS). The germ was isolated in blood culture and in joint puncture fluid. The patient received germ-sensitive antibiotic treatment for meningitis sepsis and evolved favorably. This paper describes the epidemiology of neonatal sepsis and the changes that have occurred after the administration of the antibiotic prophylaxis during pregnancy.